Architectural Images in the Miniatures of the Novgorod Psalter of Simon of the Second Quarter of the 14th Century (State Historical Museum, Chlud. 3) - Smirnova, Engelina S. (Actual Problems of Theory and History of Art, 2017)
The special feature of the illustrations of the Psalter of Simon, a Novgorod manuscript of the second quarter of the 14th century (State Historical Museum, Chlud. 3), is a large number of architectural images.The buildings depicted in the two miniatures at the beginning of the codex (fols 1v and 6v), forming the background for the main figures, have their counterparts in the Tver’ manuscript of the Chronicle of Georgios Amartolos of the late 13th — early 14th century (Russian State Library, MDA 100). The architectural structures of the second group — those in the scenes from the story of King David and in the illustrations to some Bibleverses —play the traditional role of flanking wings. However, they stand out for their voluminous cubic buildings, for their design in the form of quadras in the walls, for the presence of not only rectangular and arched, but round windows as well, and for various small towers on the roofs including the peaked ones reflecting the motifs of Gothic architecture. In the third group of miniatures, which are the illustrations to the Psalms placed in the margins of the text, there are buildings that become participants in “a dialogue” with figures standing in front of them (King David, Joasaph and others). In some instances, the cupola buildings of the Byzantine or Russian type were depicted, in the others — strongholds with rectangular outlines, with small towers, and most often with peaked towers and ciboria. Those silhouettes remind us of Gothic constructions, especially the ones in West-European Gothic manuscripts.We have a good reason to propose that the ancient prototype of the Psalter of Simon was a Russian manuscript of the 11th century with miniatures reproducing Byzantine models of the Macedonian period where the idea of the Christianization of peoples (pagans) was proclaimed. The structure of the ‘dialogue’compositions in the marginal illustrations of the Psalter of Simon, where one of the participants of the dialogue is a church building, may hark back to a hypothetical ancient prototype. Nevertheless, the Gothic appearanceof the buildings depicted in the Psalter is a contribution of cultural contacts between Novgorod and the West, which were especially intensive since the second quarter of the 13th century.